Genetic Evidence for the Actin Homolog Gene mreBH and the Bacitracin Resistance Gene bcrC as Targets of the Alternative Sigma Factor SigI of Bacillus subtilis - Tseng, Chi-Ling (American Society for Microbiology (ASM), 2008)
The Bacillus subtilis sigI gene, which is a member of the class VI heat shock genes of the B. subtilis heat shock stimulon, encodes an alternative sigma factor whose regulon is poorly defined. In this study, by using a binary vector system, we showed that B. subtilis SigI could drive expression of a transcriptional fusion between the sigI regulatory region from Bacillus licheniformis, Bacillus sp. strain NRRL B-14911, B. subtilis, or Bacillus thuringiensis and the xylE reporter gene in B. subtilis. The transcriptional initiation sites of these fusions in B. subtilis were mapped by primer extension analyses. A putative consensus promoter sequence probably recognized by the B. subtilis SigI was thus deduced. Using a consensus sequence-based search procedure, we found putative σ(I) promoters preceding the actin homolog gene mreBH and the bacitracin resistance gene bcrC of B. subtilis. Overexpression of the B. subtilis sigI gene could specifically stimulate expression of both an mreBH promoter region-bgaB fusion and a bcrC promoter region-bgaB fusion. Expression of these two fusions at the amyE locus of the B. subtilis chromosome was heat inducible and SigI dependent as revealed by sigI gene disruption experiments. Primer extension analysis showed that the identified mreBH and bcrC transcriptional start sites were at appropriate distances from their σ(I) promoter elements. This further supports the notion that SigI can directly regulate mreBH and bcrC expression. Taken together, these results strongly suggest that mreBH and bcrC are new members of the SigI regulon.